Structure aided design of a Neu5Gc specific lectin - Christopher J. Day (Nature Portfolio, 2017)
Abstract Subtilase cytotoxin (SubAB) of Escherichia coli is an AB5 class bacterial toxin. The pentameric B subunit (SubB) binds the cellular carbohydrate receptor, α2–3-linked N-glycolylneuraminic acid (Neu5Gc). Neu5Gc is not expressed on normal human cells, but is expressed by cancer cells. Elevated Neu5Gc has been observed in breast, ovarian, prostate, colon and lung cancer. The presence of Neu5Gc is prognostically important, and correlates with invasiveness, metastasis and tumour grade. Neu5Gc binding by SubB suggests that it may have utility as a diagnostic tool for the detection Neu5Gc tumor antigens. Native SubB has 20-fold less binding to N-acetlylneuraminic acid (Neu5Ac); over 30-fold less if the Neu5Gc linkage was changed from α2–3 to α2–6. Using molecular modeling approaches, site directed mutations were made to reduce the α2–3  $${\boldsymbol{\gg }}$$ ≫  α2–6-linkage preference, while maintaining or enhancing the selectivity of SubB for Neu5Gc over Neu5Ac. Surface plasmon resonance and glycan array analysis showed that the SubBΔS106/ΔT107 mutant displayed improved specificity towards Neu5Gc and bound to α2–6-linked Neu5Gc. SubBΔS106/ΔT107 could discriminate NeuGc- over Neu5Ac-glycoconjugates in ELISA. These data suggest that improved SubB mutants offer a new tool for the testing of biological samples, particularly serum and other fluids from individuals with cancer or suspected of having cancer.